PELAKSANAAN STANDARD OPERATING PROCEDURE (SOP) SERTIFIKASI HALAL OLEH MAJELIS ULAMA INDONESIA (MUI) RIAU (STUDI KASUS USAHA KATERING DI KOTA PEKANBARU) - Aldini Fitri; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Standard Operating Procedure (SOP) is guidance of work stages to perform tasks based on function and tools of work assessment made systematically in order to maintaining bureaucratic effectively and efficiently. SOP arranged to abridging, straightening, and ordering tasks which it is contained chronology of process in performing tasks from the beginning task until the last task. Therefore, in making of halal certification, LPPOM MUI as executioner of the process has arranged a plot of SOP systematically before the certification being published including catering enterprise. Facts on field that society and producer are in misperception to SOP halal licence publication. This research aimed to understand SOP of halal licence and its application to Catering Enterprise in Pekanbaru City.Theory of concept which is used by researcher is SOP theory by Purnamasari, which indicators such as Consistency, Efficiency, Minimization of Error, Problem Resolution and Working Map. This research use qualitative research method which data analyzed descriptively. In data collecting, researcher use interview technique, observation and documentation. With using technique of purposive sampling as source of information and triangulation technique as source of data validityResult of this research shows that SOP of Halal Certification by LPPOM MUI Riau generally and catering enterprise particularly is good enough, nevertheless not implemented maximally based on efficiency which is not fast by time and precise along with lack of public socialization to society or producers in Pekanbaru City. On the other hand, process that working manually made execution of certification still not fast by time and Halal Guarantee System (HGS) not fully implemented by LPPOM to catering enterprise in Pekanbaru City.Keywords: Implementation, SOP, Certification, Halal